The world according to GARP transcription factors. (October 2017) - Safi, Alaeddine; Medici, Anna; Szponarski, Wojciech; Ruffel, Sandrine; Lacombe, Benoît; Krouk, Gabriel
Highlights: GARP family contains genes with very diverse in planta functions. GARP family may contain nutrient sensor proteins. GARP TF could act as pioneer TFs. GARP TF are thus likely at the crossroads of nutrition and development in plants. Abstract : Plant specific GARP transcription factor family (made of ARR-B and G2-like) contains genes with very diverse in planta functions: nutrient sensing, root and shoot development, floral transition, chloroplast development, circadian clock oscillation maintenance, hormonal transport and signaling. In this work we review: first, their structural but distant relationships with MYB transcription factors, second, their role in planta, third, the diversity of their Cis-regulatory elements, fourth, their potential protein partners. We conclude that the GARP family may hold keys to understand the interactions between nutritional signaling pathways (nitrogen and phosphate at least) and development. Understanding how plant nutrition and development are coordinated is central to understand how to adapt plants to an ever-changing environment. Consequently GARPs are likely to attract increasing research attentions, as they are likely at the crossroads of these fundamental processes.